Analysis of Judge's Decision in Imposing Child Abuse Crime - Husnulhotima Sauri (Universitas Negeri Gorontalo, 2023)
The purpose of this research is to know and analyze abouthow to Analyze the Decision of the Gorontalo High Court Number: 2/Pid-Sus-Anak/2020/PT Gto against children as perpetrators of criminal acts of obscenity in the city of Gorontalo and to find out what factors influence the Judge's Decision in Cases of Crime of Child Abuse in Court High Gorontalo Number: 2/Pid-Sus-Children/2020/PT Gto. The type of approach used is Normative Research where the approach used is a statute approach and a case approach. The data obtained are from literature, laws, journals, and thesis. Data analysis or data management in this study was carried out in a deductive way. The results obtained in this study indicate that the judge in imposing a sentence on the perpetrator is still contrary to the principle of proportionality. Then there are several factors that influence the judge's decision, which include: 1.) Factors originating from the judge. 2) Factors originating from the defendant.